2018
DOI: 10.1021/acs.joc.8b02312
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Free Trifluoromethylation of Indazoles

Abstract: A simple and efficient tert-butyl hydroperoxide-mediated direct trifluoromethylation of indazoles using sodium trifluoromethanesulfinate has been developed under metal-free conditions. A library of trifluoromethylated products with broad functionalities has been synthesized with moderate to good yields. A radical mechanistic pathway has been proposed for the present protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(29 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…In addition, the reaction has no strict restriction on the scope of substrates,h as good functional group applicability, and providesm oderate or better yields.Areasonable mechanism has been proposed, Firstly,C uBr reacts with Ag 2 CO 3 In 2018, Ranu and co-workers also used 8-aminoquinoline as ad irecting group to carry out ortho-C-H amidation reactions of aromatic amidesw ith the acyl azides under the catalysis of Cu(II) (Scheme 10). [34] In this paper, aromatica mides and acyl azides were used as substrates, Cu(OAc) 2 as catalyst, K 2 CO 3 as base, DMSOa ss olvent, and the reactionw as completed at room temperature in 12 h. Au niquef eature of this protocoli sthat the amount of catalyst Cu(OAc) 2 has ad ecisive effect on the reaction. On the one hand, when 1equivalent amount of Cu(OAc) 2 is used as catalyst, the aroyl azide will react directlyw ith aromatic amide substrates,a nd aroyl amide productsa re mainly produced.…”
Section: Copper Catalysismentioning
confidence: 99%
“…In addition, the reaction has no strict restriction on the scope of substrates,h as good functional group applicability, and providesm oderate or better yields.Areasonable mechanism has been proposed, Firstly,C uBr reacts with Ag 2 CO 3 In 2018, Ranu and co-workers also used 8-aminoquinoline as ad irecting group to carry out ortho-C-H amidation reactions of aromatic amidesw ith the acyl azides under the catalysis of Cu(II) (Scheme 10). [34] In this paper, aromatica mides and acyl azides were used as substrates, Cu(OAc) 2 as catalyst, K 2 CO 3 as base, DMSOa ss olvent, and the reactionw as completed at room temperature in 12 h. Au niquef eature of this protocoli sthat the amount of catalyst Cu(OAc) 2 has ad ecisive effect on the reaction. On the one hand, when 1equivalent amount of Cu(OAc) 2 is used as catalyst, the aroyl azide will react directlyw ith aromatic amide substrates,a nd aroyl amide productsa re mainly produced.…”
Section: Copper Catalysismentioning
confidence: 99%
“…Only two articles are available in the literature. [58,63] Togni et al reported an example of N-2 trifluoromethylation of 2Hindazole. Silylation of 2H-indazole (66 a) took place in situ with the help of 1,1,1,3,3,3-hexamethyldisilazane (HMDS) and a catalytic amount of silica sulfuric acid (SSA) and then trifluoromethyl group was introduced in presence of 66 c as CF 3 source, HNTf 2 and LiNTf 2 as catalyst.…”
Section: Trifluoromethylationmentioning
confidence: 99%
“…Our group has developed several functionalization methods for indazole derivatives. [63][64][65][66][67][68] indazole, herein, we first report a brief review on direct functionalizations including arylation, alkylation, acylation, alkenylation, alkynylation, trifluoromethylation, selenylation, nitration, cyanation, bromination, carbonylation and oxyalkylation of indazole derivatives. This article covers most of the related papers published in the last 20 years.…”
Section: Introductionmentioning
confidence: 99%
“…Despitei ts importance, not many reports are available [18][19][20][21] relative to the numerous reports on substituted 1H-indazoles, [22][23][24][25][26] presumably because of the low reactivity at C3 position of 2H-indazoles [27][28][29] arising from their less aromatic character of quinonoid form [27][28][29] that obstructs formation of functionalized or fused derivatives.Of the functionalized 2H-indazoles, non-arylated scaffolds have been synthesized by C3 alkenylation, [30] annulation, [31] acylation, [27] phosphonylation, [32] nitration, [33] andt rifluoromethylation. [34] However,f ar fewer attempts have been made for the direct arylation of 2H-indazolesa tt he C3 position, including a few reports of Negishic ross-coupling [35] and arylation by aryl halides, [36][37][38][39] which required Cu or Pd metal catalysts, expensive ligands, andmany additives (base, oxidant) with long reaction times (Scheme 1). In light of this, we report herein a straightforward methodology for the direct arylation of 2H-indazolesw ithout the use of metal, ligand, or externalo xidant (Scheme1).…”
mentioning
confidence: 99%
“…Of the functionalized 2H-indazoles, non-arylated scaffolds have been synthesized by C3 alkenylation, [30] annulation, [31] acylation, [27] phosphonylation, [32] nitration, [33] andt rifluoromethylation. [34] However,f ar fewer attempts have been made for the direct arylation of 2H-indazolesa tt he C3 position, including a few reports of Negishic ross-coupling [35] and arylation by aryl halides, [36][37][38][39] which required Cu or Pd metal catalysts, expensive ligands, andmany additives (base, oxidant) with long reaction times (Scheme 1). In light of this, we report herein a straightforward methodology for the direct arylation of 2H-indazolesw ithout the use of metal, ligand, or externalo xidant (Scheme1).…”
mentioning
confidence: 99%